Soviet Politics and Diplomacy in the Far East: Strategies and Alliances on the Eve of and During World War II - Yu. A. Dubinin (Vestnik MGIMO-Universiteta)
This article offers an in-depth analysis of Soviet policy and diplomacy in the Far East during the tumultuous period spanning from the 1920s to the 1940s. These policies were profoundly shaped by two key factors: firstly, the ideological considerations rooted in the political framework established in the USSR following the 1917 revolution, and secondly, the geopolitical dynamics reflecting the evolving global and regional political landscape in the Far East. The ruling Bolshevik Party and the Soviet government faced formidable challenges as they sought to safeguard the nascent Soviet Republic amid mounting international tensions, both on a global scale and within the Asia-Pacific region.This study aspires to present a comprehensive and integrated examination of Soviet policy and diplomacy during this era. It delineates four distinct chronological segments, each characterized by its unique features, priorities, and challenges. At the same time, these segments are united by the overarching goal of consolidating the Soviet Union's position in the Far Eastern region and the broader Pacific theater. The four discernible stages in Soviet policy and diplomacy in the Far East encompass:1.    The period spanning from 1927 to 1932, marked by an initial deterioration in relations between the Soviet government and the Kuomintang administration following the 1927 split between the Kuomintang and the Communist Party of China (CPC). This phase also witnessed the 1929 conflict on the Chinese Eastern Railway and culminated in the reestablishment of Sino-Soviet relations, all set against the backdrop of escalating Japanese aggression in Northeastern China (Manchuria). This phase demanded adroit diplomacy balancing strength and strategic statecraft.2.    The 1930s, especially in the aftermath of Japan's aggressive incursions into China, saw limited interaction and collaboration between the USSR and the Republic of China. This period featured cautious Soviet-Japanese relations and included significant events such as armed clashes at Lake Khasan and the Khalkhin-Gol River, as well as the signing of the USSR-Japan Neutrality Pact.3.    The era of the Great Patriotic War from 1941 to 1945, during which the Soviet Union's foremost objective was the defeat of the German Nazi aggressor. During this period, Soviet diplomacy was primarily preoccupied with relations with Anglo-American allies, with particular emphasis on the contentious issue of opening a second front. Consequently, Far Eastern and Pacific policy concerns assumed a somewhat marginalized role within the realm of Soviet diplomacy.4.    Finally, the period spanning from the winter to the summer of 1945 emerged as a pivotal juncture. During this time, the Soviet Union intensified its political, diplomatic, and military involvement in the Far East, all against the backdrop of preparations for the impending entry into the war against Japan. Diplomatic endeavors reached their zenith during this critical phase.